Pengaruh Waktu Pemerahan dan Tingkat Laktasi terhadap Kualitas Susu Sapi Perah Peranakan Fries Holstein - Mardalena, Mardalena (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
This study intended toÂ know theÂ difference of milk quality result of pressing out of evening and morning at level of lactation (I, II and III) of Fries Holstein dairy cattle. Experimental design used in this experimentÂ was CompleteÂ RandomizedÂ DesignÂ (CRD)Â Factorial 2x3 PatternÂ byÂ 10Â times replication. The result indicated that quality of milk at pressing out of morning were fat rate (3,17%), dry materials rate ( 12,206%) and protein rate ( 3,583%)was lowerÂ thanÂ pressing out of evening which wereÂ fat rate ( 3,69%), dry materials rate ( 12,527%) and protein rate ( 3,613%). Conclusion of this research wasÂ the quality of milk when pressing out morningÂ lower thanÂ evening. Level of lactationÂ didnâ€™tÂ influence the quality of milk.